Recent progress in diamond radiation detectors. Issue 1 (2nd January 2021) - Shimaoka, T.; Koizumi, S.; , J. H.; Kaneko,
Abstract: This paper reviews recent progress in diamond radiation detectors. Diamond is an ultra-wide gap (5.5 eV) semiconducting material which has several ideal properties for radiation detectors, such as solar blindness, high temperature operation, and fast response. Furthermore, diamond has near tissue-equivalence due to its low atomic number ( Z = 6) and chemical stability due to its strong covalent bonds. Because of these features, diamond has long been used as a radiation detector in the fields of nuclear engineering, nuclear fusion, high energy physics and medical therapy. Until the 1990s, most of the research was conducted using selected high purity natural diamonds. Since the 2000s, the detector characteristics of synthetic diamond detectors have been greatly improved by achieving high purity diamond by microwave plasma enhanced chemical vapor deposition (CVD). Single-crystal CVD diamonds present best characteristics for spectroscopy in diamond radiation detectors. For applications requiring large sensitive areas, polycrystalline CVD diamond is mostly used. Heteroepitaxial diamond detectors are a promising alternative to increase the area of spectroscopic diamond radiation detectors. For applications in extreme environments, high radiation flux which leads to polarization effects is a crucial issue. Even with diamond, which has excellent radiation hardness, degradation of detector characteristics due to irradiation is inevitable. Detectors designed with small carrier travel distances, such as membrane diamond detectors and three-dimensional diamond radiation detectors, are effective ways to mitigate the degradation.